EFEKTIFITAS PEMBELAJARAN SKILL LAB DENGAN MEDIA VIDEO PEMBELAJARAN DARING TERHADAP MODUL PRAKTIKUM SKILL LAB - Sunaryo Joko Waluyo; Siti Nur Solikah (UNIVERSITAS SARI MUTIARA INDONESIA, 2021)
Background, The Covid-19 (Coronavirus Disease-2019) pandemic has spread to almost all parts of the world since the end of 2019. The Indonesian government has provided various strategies to prevent the spread of the Coronavirus, which comprehensively affects all levels of Indonesian society. One of the Indonesian government policies that has a wide impact is government regulation in the field of education, both in the professional area and in the field of administration and the environment. With the pandemic, the implementation of educational activities has changed in various forms of learning activities, both theoretical and practical learning, all of which must run online. Purpose, This study aims to determine the effectiveness of learning lab skills using Online Learning Video Media on the Skill Lab Practicum Module for fourth-semester students of the Diploma Three Nursing Study Program, Insan Husada Polytechnic Surakarta. Methods, Lab skill practicum is called a control group. This study is a quasi-experimental study with a post-test only control design, the samples were selected and grouped into the experimental group, and the control group, the group that was treated with the provision of online learning videos, was called the experimental group, while the group that was not given online learning videos and only received the module. The experimental group was 47 students, and the control group was 46 students. Result, (1) There is a difference in the test scores of respondents who learn using the video skill lab media with those who use the skill lab practicum module media. (2) The average value of respondents who received learning using video media was 86.02, higher than respondents who received learning using the practicum module, which was 81.38 Conclusion, The skill lab learning model using video is more effective than using the practicum module for practicum learning on nursing actions for physiological reflex examinations